(untitled) (Bangladesh Journal of Botany, 2019)
Since the seeds of endemic Ajuga vestita are difficult to germinate naturally they were subjected to in vitro culture. Highest rate of germination was obtained in 1/4 MS medium supplemented with 30 g sucrose in light. Microshoots subcultured in 1/1 MS supplemented with 0.125 mg/l Kn rooted well and transferred to soil with 80% success.